2015
DOI: 10.1111/epi.12966
|View full text |Cite
|
Sign up to set email alerts
|

Mesial temporal lobe epilepsy with hippocampal sclerosis is a network disorder with altered cortical hubs

Abstract: SUMMARYObjective: Electrophysiologic hubs within the large-scale functional networks in mesial temporal lobe epilepsy (mTLE) with hippocampal sclerosis (HS) have not been investigated. We hypothesized that mTLE with HS has different resting-state network hubs in their large-scale functional networks compared to the hubs in healthy controls (HC). We also hypothesized that the hippocampus would be a functional hub in mTLE patients with HS. Methods: Resting-state functional networks, identified by using magnetoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 39 publications
(112 reference statements)
2
40
0
Order By: Relevance
“…This suggests a specific network of propagations and a large-scale functional network as recent functional imaging studies, especially connectivity studies, have revealed it [16,17].…”
Section: Tle-hs: a Distinct Network Syndrome?mentioning
confidence: 78%
“…This suggests a specific network of propagations and a large-scale functional network as recent functional imaging studies, especially connectivity studies, have revealed it [16,17].…”
Section: Tle-hs: a Distinct Network Syndrome?mentioning
confidence: 78%
“…This changed connectivity could certainly be important given that limbic seizures are known to propagate through the thalamus in both human and animal models (Blumenfeld et al, 2004; Guye et al, 2006; Patel et al, 1988; Sloan et al, 2011). Additionally, MEG analysis was able to demonstrate the presence of hub-like regions in both temporal cortex and hippocampus of patients with TLE that do not exist in control subjects, and the importance of hubs to excitability was discussed earlier (Jin et al, 2015). …”
Section: Network Organization At the Macrocircuit Level: Applicatiomentioning
confidence: 81%
“…In TLE, while most seizures originate in the hippocampus [66], the epileptogenic network has been shown to often extend to entorhinal, lateral temporal, and inferior frontal cortices as well, together with subcortical nuclei, such as the amygdala and medial thalamus [61,62]. Offering a synoptic view on brain dynamics at a millisecond scale, electrophysiological studies employing electroencephalography (EEG) and magnetoencephalography (MEG) not only have been of high utility in characterizing changes at seizure onset but also could reveal chronic changes in local and distributed activity [67,68]. Notably, studying statistical relationships between time series has been used to evaluate dynamic changes in interregional connectivity; moreover, electrophysiological techniques provide a range of spectral (i.e., frequency-dependent) markers that have the potential to probe tissue epileptogenicity in vivo.…”
Section: Evidence Justifying the Study Of Tle As A Network Disordermentioning
confidence: 99%